The Federal Anti-Trust Law - Dunn, Charles Wesley (Columbia University Press, 1930)
A collection of lectures delivered at the School of Business of Columbia University in 1929 on the broad study of the principal antitrust acts and their application to business concentration and the resulting major problems of trade relationship. Specifically addresses the Sherman, Clayton, and Federal Trade Commission Acts